Soft Tissue Coverage in Distal Lower Extremity Open Fractures: Comparison of Free Anterolateral Thigh and Free Latissimus Dorsi Flaps - Philandrianos, Cécile; Moullot, Pierre; Gay, André M.; Bertrand, Baptiste; Legré, Régis; Kerfant, Nathalie; Casanova, Dominique (Journal of Reconstructive Microsurgery, 2018)
Background When microsurgical transfers are required in posttraumatic lower limb reconstruction, surgeons must choose among many types of free flaps. Historically, surgeons have advocated muscular flaps for coverage of open lower extremity wounds, but fasciocutaneous free flaps are now often used with good results. This study aimed to compare the functional and aesthetic outcome of reconstruction by free muscular latissimus dorsi (LD) flap and free fasciocutaneous anterolateral thigh (ALT) flap used for soft tissue coverage of distal lower extremity open fractures.Methods We performed a single-center, retrospective study of subjects with distal lower limb open fractures treated with LD flaps or ALT flaps between 2008 and 2014. Patients with limited follow-up or incomplete data were excluded from the analysis. Donor and recipient sites, early complications and long-term outcomes (functional and aesthetic) were studied and compared according to the type of flap.Results A total of 47 patients were included: 27 patients in the LD flap group and 20 patients in the ALT flap group. No significant difference was found regarding early and late complications and long-term functional outcomes (bone healing, infectious bone complications, flap healing). As for aesthetic outcome and donor-site morbidity, reconstruction using the ALT free flap had significantly better results (p < 0.05).Conclusions In posttraumatic lower limb injury, either LD or ALT free flaps can be used for wound coverage with comparable long-term functional outcomes. The ALT flap provides better cosmetic results than LD.
Keywords: anterolateral thigh flap; latissimus dorsi flap; free flap; lower limb; open tibial fracture; open foot fracture